Village Funds Mismanagement in Policy Evaluation Perspective in Jejangkit Pasar Village of South Kalimantan - Taufik Arbain; Erma Ariyani (Indonesian Association for Public Administration (IAPA), 2019)
The village fund policy is implemented to improve infrastructure development, community development and empowerment towards a prosperous village. However, the management of village funds did not meet expectations, due to lack of community participation in supervision. The purpose of this study is to analyze the mismanagement of village funds using a policy evaluation perspective. This research emphasizes the approach qualitative- evaluative, to explain the phenomena found in the field. This study found that mismanagement of village fund was not only caused by weak supervision and low human resources but also caused by the dominant, undemocratic and oligarchic aspects of leadership which had implications for the powerlessness of village actors in managing village funds in accordance with procedures, accountability, and transparency. Moreover, the formulation stage of the policy on the use of village funds is only a formality so that the power of the leader (the Village Head) cannot be implemented in the ethics of public administration and good governance.